IMPLEMENTASI PENDIDIKAN KARAKTER SISWA DI SD NEGERI 29 RANTAU BATU PASAR - Wahdini, Wahdini; Elvina, Elvina (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
As the first formal educational institution, elementary schools have a significant responsibility in developing the character of their students. At this stage, students are at a crucial stage before continuing their education to a higher level, so strengthening character education is crucial. This study aims to describe the implementation of character education at SD Negeri 29 Rantau Batu Pasar, which includes planning, implementation, evaluation, and strengthening of school culture. The approach used is descriptive qualitative, through interviews with the principal, teachers, students, and parents. The results indicate that the characters of discipline, responsibility, religiosity, mutual cooperation, and integrity are realized through daily habits and activities, teacher collaboration, and support from the school committee. Meanwhile, the main obstacles are consistency of implementation, time constraints, and uneven parental involvement. Recommendations include strengthening planning based on measurable indicators, character assessments, and sustainable school-family-community partnerships.